128k views
5 votes
5x + y = 2
2x-3y = 62

1 Answer

2 votes

Hey there! :)

Answer:

x = 4, y = -18 or (4, -18).

Explanation:

Given:

5x + y = 2

2x - 3y = 62

We can use substitution to solve this problem. Rearrange the first equation in terms of y:

5x + y = 2 ---> y = -5x + 2

Substitute in this equation for y into the second equation:

2x - 3(-5x + 2) = 62

Distribute -3:

2x + 15x - 6 = 62

Combine like terms:

17x - 6 = 62

Add 6 to both sides:

17x = 68

Divide both sides by 17:

x = 4.

Plug in this value for x into an equation to solve for y:

5(4) + y = 2

20 + y = 2

y = -18.

Therefore, the solutions to this system of equations are:

x = 4, y = -18 or (4, -18).

User NascarEd
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.